Genetics and Light Affect Grouping Behavior in Red Flour Beetles - Jimenez, Bricelis; Marshall, Jeremy (My University, 2018)
Although others may see beetles as pests, entomologists would say otherwise. These critters vary in sizes and can be found almost anywhere! Interaction amongst humans and animals within an environment can be pretty similar whether it is environmentally influenced or through genetic material. We often question if habits are done because of genes or because of what is going on around us. Although beetles do not seem interesting, they actually have their own way of socializing. Beetles do not really have the best vison, however they can socialize/communicate using pheromones. Chemical messages are chemicals integrated with behavior (Birch, 1976). Using red flour beetles from Mantitoba, Canada (NDG) and Hudson, Kansas (Hudson) we can see how these beetles from two different areas interact amongst each other. Will there be a distinct isolation due to there strains and if so does this affect how they are within the same strain.
Keywords: Fall 2018